Análisis de la capacidad de fermentación de los residuos de piña (ananas comosus) para la obtención de biogás (2017)
In order to decrease fossil fuel consumption and increase the sustainability of Colombian company Fruandes, it is proposed a way of re-using pineapple peel waste (ananas comosus) as a source of biomass to produce methane-rich biogas, so that the costs of natural gas used for production processes are reduced. Biogas is obtained by the anaerobic fermentation of pineapple peels, using a sample of brine from Zipaquirá, Colombia, as the inoculum. This study aims to analyze the fermentative capacity of the biomass and shows the implementation of a chemical pretreatment using acetic acid 0.2M at 105ÀC for one hour. It was found that the pretreatment is not fully effective in hydrolyzing the structural carbohydrates (cellulose and hemicellulose), since it hydrolyzed only 1% of the cellulose. Fermentations were carried out with 15g of solid substratum (12g of volatile solids) throughout 27 days at mesophilic conditions, and a one-way analysis of variance was proposed in order to find the effects of pretreatment in biogas production. The best yield was obtained with no treated pineapple waste, with an average biogas production of 250 cm3/gVS, where approximately 85% approximately was methane.